ANALISIS PERSEDIAAN PADA CV PETERNAKAN NUSANTARA TELUR LOKAL CABANG 1 KOTA SORONG - Liawan, Calvin; Muda, Markus Muda; Hursepuny, Prissilia (Jurnal Pitis AKP, 2022)
Inventory is the most important part in the company's operations, without inventory the company will experience the risk of losing profits because it does not have a supply of supplies to meet the needs of consumers. In inventory, there are three methods for valuing inventory using the fifo and average methods. The inventory method itself can be useful for determining inventory valuation in the company. Fifo (First In First Out) is a way of storing inventory where the goods that come in first will be sold first. While the AVERAGE (average) method is a method commonly used to calculate the cost per unit of inventory by means of a weighted average. This study aims to analyze inventory, analyze the comparison of the Fifo and AVERAGE methods and determine the methods that can be used by the company.